2020
DOI: 10.1016/j.tbs.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the desire for using public transport

Abstract: The desire to use public transport, or use it more frequently, can be an important indicator of people's intention to travel by public transport. However, the desired and relative desired travel amount (wanting to travel less or more) in the context of public transport use has not yet been analyzed. In this paper, we examine the relationship between actual and desired public transport frequency of 986 students of Laval University, Canada. Results indicate that most respondents have a desired public transport f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 46 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…In line with recent research [44] which concluded that more frequent travel with public transport (than desired) may negatively impact attitudes and satisfaction, the present results suggest that the frequency of public transport travel also appears to have a negative impact on perceived accessibility. Thus, individuals traveling more frequently with public transport also experience their accessibility as lower than people who travel less often.…”
Section: General Findings In Light Of the Structural Model And The Hysupporting
confidence: 91%
“…In line with recent research [44] which concluded that more frequent travel with public transport (than desired) may negatively impact attitudes and satisfaction, the present results suggest that the frequency of public transport travel also appears to have a negative impact on perceived accessibility. Thus, individuals traveling more frequently with public transport also experience their accessibility as lower than people who travel less often.…”
Section: General Findings In Light Of the Structural Model And The Hysupporting
confidence: 91%
“…Carrus et al (2008) found that positive anticipated emotions of travelling by PT have a positive effect on the desire to use PT instead of the car. A similar effect-of satisfaction with PT use on the desire to use PT-was found by De Vos et al (2020). Lai and Chen (2011) found that the intention to use PT is positively affected by satisfaction with PT, while Carrus et al (2008) found that anticipated emotions of travelling by PT (in the two weeks after measurement) affect the intention to use PT instead of the car.…”
Section: The Effect Of Past Behaviour and Travel Satisfaction On Travel Behavioursupporting
confidence: 60%
“…Although our sample may not be fully representative of the students at Laval University, it is relatively large in size, which makes it possible to estimate specific relationships with ample confidence. For more information regarding the recruitment of participants and sample characteristics, see De Vos et al (2020).…”
Section: Datamentioning
confidence: 99%
“…Studies of desire have mainly focused on desired travel amounts (Mokhtarian & Salomon, 2001;Redmond & Mokhtarian, 2001), although some studies analysed the desired use of a certain travel mode (e.g. public transport (Carrus, Passafaro, & Bonnes, 2008;De Vos, Waygood, & Letarte, 2020a)).…”
Section: Introductionmentioning
confidence: 99%